Protibolečinska učinkovitost transkutane električne nevrostimulacije (TENS) na živalskih modelih in mehanizem njenega delovanja - Salihović, Mensur (Zdravniški vestnik, 2013)
Transcutaneous electrical nerve stimulation (TENS) has been used to reduce intensity and unpleasentness of pain for several decades. Findings of clinicalstudies about its effectivenes are not conclusive. On the contrary, the results from the studies on animal models of pain, which allow better control of experimental conditions, unequivocally demonstrate the effectiveness of TENS in reducing nociceptive activity. The mechanism of TENS action is not known. In the present review, the proposed basic mechanisms of analgesic action of TENS are summarized.
Keywords: analgezija; bolečina; električno draženje; TENS; therapy; zdravljenje